2019
DOI: 10.1111/ijpo.12524
|View full text |Cite
|
Sign up to set email alerts
|

Association between grandparent coresidence and weight change among first‐grade Japanese children

Abstract: Summary Background The prevalence of grandparent coresidence is increasing. However, the impact of grandparent coresidence on weight change among school‐age children remains unclear. Objectives The objective of the study is to examine the association between grandparent coresidence and obesity‐related behaviours and change in body mass index (BMI) z scores among school‐age children. Methods In total, 3422 caregivers of first‐grade children in Adachi City, Tokyo, participated in surveys and health checkups in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…The remaining 23 studies that examined the relationship between grandparental child care and children's body weight status were included in the review. 16,17,[19][20][21][22][23][24][25][26][27][28][29][32][33][34][35][36][37][38][39][40][41] Fourteen studies were included in the meta-analyses, as shown in Table 4 (4 studies on BMI z-scores 32,33,37,38 and 10 studies on childhood overweight/obesity risk 19,[22][23][24][25][26]28,[34][35][36] ). Table 2 summarizes the basic characteristics of the 23 included studies.…”
Section: Study Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 23 studies that examined the relationship between grandparental child care and children's body weight status were included in the review. 16,17,[19][20][21][22][23][24][25][26][27][28][29][32][33][34][35][36][37][38][39][40][41] Fourteen studies were included in the meta-analyses, as shown in Table 4 (4 studies on BMI z-scores 32,33,37,38 and 10 studies on childhood overweight/obesity risk 19,[22][23][24][25][26]28,[34][35][36] ). Table 2 summarizes the basic characteristics of the 23 included studies.…”
Section: Study Quality Assessmentmentioning
confidence: 99%
“…They also found that grandparents' involvement in caregiving was inversely associated with BMI z-scores among children 6-10 years of age from certain Hispanic origin groups. 17 Morita et al 38 reported grandparents' co-residence to be inversely associated with BMI z-scores among children 6-7 years of age. Lindberg et al 39 reported that receiving emotional support from paternal grandparents was inversely associated with BMI z-scores among children 4-6 years of age.…”
Section: Key Findings Of the Included Studiesmentioning
confidence: 99%
“…The Adachi Child Health Impact of Living Difficulty (A-CHILD) project was established in 2015 to evaluate the determinants of health among children in Adachi City, Tokyo, Japan [30][31][32]. We used data from the 2018 wave of the A-CHILD study.…”
Section: Study Design and Subjectsmentioning
confidence: 99%
“…Children's physical activity was assessed using the frequency of physical activity for 30 min or more during the week (never/rarely, 1-2 times/week, 3-4 times/week, or ≥5 times/week). Children's eating behavior included frequency of vegetable intake (twice/day, once/day, or <3 times/week), frequency of breakfast intake (every day, often, or rarely/never), and snacking habits (no snacking, snacking at a set time (controlled), or snacking freely) [32]. Household characteristics included the caregiver's marital status (married or living with partner, single, divorced, or widowed), the child having siblings (yes or no), cohabitation with the child's grandparents (yes or no), and annual household income (<3.00, 3.00-5.99, 6.00-9.99, or ≥10.0 million yen).…”
Section: Covariatesmentioning
confidence: 99%
“…Family and the home environment are well-established sources of influence on children’s eating habits, especially in early and middle childhood [6]. While poor parental feeding practices such as using unhealthy food to reward desirable child behavior [7] and overfeeding [8] can adversely affect children’s dietary behaviors and their health, there is growing evidence to suggest that grandparents play an increasingly important role in influencing their grandchildren’s feeding practices [8,9,10,11,12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%